Fiscal Policy Cannot Relieve Everyone - Jens Boysen-Hogrefe (Wirtschaftsdienst)
Abstract The coming relief packages should be precisely targeted in the form of transfers for those on low incomes. In times of inflation, the efficiency of government fiscal policy is of particular importance. Additional spending projects should be critically examined accordingly. In the face of acute shortages, it may be plausible to postpone projects. Recent developments in commodity markets suggest that some shortages may not be permanent. The possibility that some of the calamities are temporary argues for not betting on new taxes now. An increase in the tax ratio that allows for a temporarily more progressive design of the tax and transfer system is already endogenous. To this end, however, the “cold progression” should not be dismantled (as has been customary in recent years), as this would probably constitute an expansionary impulse in itself in the coming year.